The Influence of Digital Platform Capability on Organizational Agility Mediated by Human Capital on SMEs - Mulkan Teguh Sutrisno; Mis Widya Andelina; Abdul Malik (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the influence of digital platform capability on organizational agility, mediated by human capital in Small and Medium Enterprises (SMEs). Data were collected through a survey using questionnaires distributed to 100 respondents from various SMEs in Semarang. The analytical technique employed in this research is Structural Equation Modeling (SEM), processed using SPSS version 26 software. The results indicate that digital platform capability has a positive and significant effect on organizational agility (p < 0.05). Additionally, human capital significantly mediates the relationship between digital platform capability and organizational agility, meaning the impact of digital platforms on organizational agility is stronger when SMEs possess skilled human resources capable of optimally utilizing digital technologies. In conclusion, to enhance organizational agility, SMEs should focus on developing human capital that can effectively integrate digital technologies into daily business operations. Keywords: Digital Platform Capability, Organizational Agility, Human Capital, SMEs.